Cold Kit Labeling: The Future of 68Ga Radiopharmaceuticals? - Lepareur, Nicolas (Frontiers in Medicine, 2022)
Over the last couple of decades, gallium-68 (68Ga) has gained a formidable interest for PET molecular imaging of various conditions, from cancer to infection, through cardiac pathologies or neuropathies. It has gained routine use, with successful radiopharmaceuticals such as somatostatin analogs ([68Ga]Ga-DOTATOC and [68Ga]GaDOTATATE) for neuroendocrine tumors, and PSMA ligands for prostate cancer. It represents a major clinical impact, particularly in the context of theranostics, coupled with their 177Lu-labeled counterparts. Beside those, a bunch of new 68Ga-labeled molecules are in the preclinical and clinical pipelines, with some of them showing great promise for patient care. Increasing clinical demand and regulatory issues have led to the development of automated procedures for the production of 68Ga radiopharmaceuticals. However, the widespread use of these radiopharmaceuticals may rely on simple and efficient radiolabeling methods, undemanding in terms of equipment and infrastructure. To make them technically and economically accessible to the medical community and its patients, it appears mandatory to develop a procedure similar to the well-established kit-based 99mTc chemistry. Already available commercial kits for the production of 68Ga radiopharmaceuticals have demonstrated the feasibility of using such an approach, thus paving the way for more kit-based 68Ga radiopharmaceuticals to be developed. This article discusses the development of 68Ga cold kit radiopharmacy, including technical issues, and regulatory aspects.